NATIONAL DEBT MANAGEMENT STRATEGIES TO MAINTAIN FISCAL STABILITY DURING A CRISIS - Albert Yansen; M. Asbullah; Pirmanta Pirmanta (Adisam Publisher, 2025)
This study discusses the state debt management strategy in maintaining fiscal stability amid the economic crisis. Using a qualitative approach based on literature review, this study analyses various policies and instruments implemented by the government, such as diversification of financing sources, exchange rate and interest rate risk management, and optimisation of debt funds for productive projects. The findings indicate that effective debt management must be based on the principles of prudence, transparency, and accountability, and supported by solid fiscal and monetary policy coordination. Additionally, key challenges include declining government revenue, global financial market volatility, and limited fiscal space due to increased debt repayment burdens. With adaptive strategies and good governance, government debt can be an important instrument to support economic recovery and maintain fiscal sustainability, provided it is used productively and in a measured manner.